Propagation of elastic wave in solid layer-liquid system - GRABOWSKA, Anna (Archives of Acoustics, 1979)
The paper presents the solution of the problem of a flat wave propagating without attenuation along a solid layer placed between a semispace filled with liquid and the vacuum. The wave equation of scalar and vector potentials of displacement has been solved for this case. A characteristic equation accounting for boundary conditions has been derived. This equation has been solved numerically and it has been shown that in these conditions the wave can propagate at a velocity slightly smaller than the wave velocity in the liquid. The distributions of stress, acoustic pressure, and displacement of the propagating wave have been determined numerically for a layer of a thickness a = 0.075 cm and a = 0.010 cm, contacting with water on one side, and for a frequency of 3 × 10^6 Hz. The type of wave is close to a surface wave.